2015
DOI: 10.1080/0972060x.2015.1004120
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Three Essential Oils againstColletotrichum acutatum, the Causal Agent of Strawberry Anthracnose

Abstract: The antifungal effects of thyme, cinnamon bark and clove bud essential oils (EOs) were investigated in vitro on Colletotrichum acutatum mycelial growth, conidial germination, appressoria formation, and in vivo on strawberry fruit disease incidence. All tested EOs, incorporated in potato-dextrose agar, inhibited C. acutatum mycelial growth, and had a fungistatic effect at concentration 667 μl/l of medium. Volatiles of cinnamon bark, thyme and clove bud EOs completely prevented conidial germination at the lowest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 30 publications
7
16
0
1
Order By: Relevance
“…Results showed that inhibitory activity of CEO was significantly correlated with the concentration of CEO. In present study, the spore germination was more sensitive to CEO treatment than mycelial growth, which was in accordance with previous studies ( Duduk et al, 2015 ). CEO had a fungistatic effect against mycelial growth of C. acutatum isolated from strawberry anthracnose at 0.667 μL/mL.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Results showed that inhibitory activity of CEO was significantly correlated with the concentration of CEO. In present study, the spore germination was more sensitive to CEO treatment than mycelial growth, which was in accordance with previous studies ( Duduk et al, 2015 ). CEO had a fungistatic effect against mycelial growth of C. acutatum isolated from strawberry anthracnose at 0.667 μL/mL.…”
Section: Discussionsupporting
confidence: 94%
“…CEO had a fungistatic effect against mycelial growth of C. acutatum isolated from strawberry anthracnose at 0.667 μL/mL. Meanwhile, CEO completely prevented the spore germination and appressorium formation at 0.00153 μL/mL ( Duduk et al, 2015 ). In addition, CEO strengthens its merits as a post-harvest fungicide against food-borne pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may contribute to the buildup of food-borne bacteria and may pose a food safety risk to consumers since small fruits are eaten fresh. Also, small fruits have a very short shelf life due to their susceptibility to spoilage pathogens, physiological disorders and mechanical injury [2]. This is partly due to their high nutrient content and water activity, and low pH which make them susceptible to fungal attack.…”
Section: Introductionmentioning
confidence: 99%
“…Astracanicum on some selected gram-negative bacteria and concluded on the antimicrobial activity and its potential usefulness [79]. According to Nataša et al, thyme, cinnamon bark and clove bud essential oils were effective against Colletotrichum acutatum mycelial growth of strawberry [80]. The cell destruction of these pathogens is as a result of the ability of the hydrophobic compounds in the essential oils to disrupt the microorganism's cell membrane, which results in change of cell morphology, alteration of membrane permeability and leakage of electrolytes [81].…”
Section: Citrusmentioning
confidence: 99%